Environmentally Conscious Principles In Event Management - Vigh, Katalin; Szeberényi, András; Dióssi, Katalin (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
From a corporate perspective, events are not only costly undertakings, but also pose substantial challenges in complying with environmental regulations and standards. In recent years, environmental, social and governance (ESG) requirements have introduced conditions whose fulfilment often entails significant financial and resource-related burdens. This research examines the event types organised by companies, such as exhibitions, conferences and internal corporate events, through the lens of environmental considerations. In a literature review an international overview of sustainable event management is assembled as a background for deeper understanding the general issues of the industry. As primary research, we conducted semi-structured interviews with eight experts in 2024/25, through which we obtained up-to-date insights into the sustainability efforts and challenges faced by Hungarian companies in the context of event organisation. The sampling strategy applied in this study followed a combination of purposive, expert, and maximum variation sampling. The study contributes to the emerging literature on green event management by outlining the organisational, regulatory and cultural factors shaping adoption. The paper concludes with managerial implications and recommendations for enhancing supplier capacity and reducing cost barriers, while highlighting directions for further research on recycling systems and environmental education in event contexts.